A review of community management of paediatric burns. Issue 8 (December 2015) - Cox, S.G.; Martinez, R.; Glick, A.; Numanoglu, A.; Rode, H.
Highlights: Domestic incidents are mostly responsible for thermal injuries in children. Children commonly receive sub optimal early burn wound management. Pre hospital management of paediatric burns is reviewed. Hydrotherapy is effective as emergency treatment. Adequate analgesia remains a major problem. Abstract: This study was a component of a broader review to evaluate burn care in South Africa. A prospective audit of 353 children with thermal injuries admitted to the Red Cross War Memorial Children's Hospital in Cape Town was performed during 2012/2013. The audit was based to assess the adherence of initial burn management to the provincial policy guidelines on the clinical management of the burn wound. The community management of each patient prior to admission to a burns centre was assessed for the following: basic demographics, emergency home management, wound cover, analgesia and transport to medical facilities. Their ages ranged from 1 month to 14 years. The average total body surface area [TBSA] was 15% [1–86%]. Most of the injuries were due to hot water accidents [78.5%] followed by flame burns (9%), direct contact and electricity burns. Two hundred and twenty five children [63%] received first aid measures at home, including cooling with water [166] ice [30] and a cooling agent. No cooling was instituted in 130 and 65% of the patient's wounds were cooled for 10 min or less. Eighty percent proceeded to the referral centre or burns unit without their wounds being covered; with only 19 patients having any medical type of dressing available at home. Two hundred and ninety five children [83.6%] received pain medication prior to admission at the burns unit. Of the 316 patients not directly attending the burns unit, 137 received IV fluids of which 95 had burns greater than 10% TBSA. None of the patients were in shock on admission and all IV lines were functioning. Forty-four children with burns greater than 10% did not receive IV fluids. The audit identified six factors that were inadequately addressed during the pre-admission period: first aid, cooling of the wound, early covering of the wound, resuscitation, pain management and transfer. If these could be readdressed, basic burn care would be substantially improved in the study area.